Introduction to Design and Analysis / A Student's Handbook - Keppel Geoffrey; Saufley William H; Tokunaga Howard (W. H. Freeman And Company, 1998)
Experimental Design and Preliminary Data Analysis, Introduction to Experimental Design, Preliminary Data Analysis, The Analysis of Single-Factor Experiments, The Logic of Hypothesis Testing, Calculating the F Ratio, Evaluating the F Ratio, Analytical Comparisons in the Single-Factor Design, Estimating Population Means and Effect Size, Errors of Hypothesis Testing and Statistical Power, The Analysis of Factorial Design, Introduction to the Analysis of Factorial Experiments, Analytical Comparisons in the Factorial Design, The Analysis of Within-Subject Designs, The Single-Factor Within-Subjects Design, The Mixed Within-Subjects Factorial Design, The Two-Factor Within-Subjects Design, Additional Statistical Procedures, The Analysis of Categorical Data, Correlation and Regression, Additional Topics, Appendices, Glossary: Significant Terms and Concepts, References, Author and Subject Index.